Microbial and Heavy Metal Contamination in Five Brands of Kohl Used in Sulaimani City - Rasheed, Banaz O.; Ali, Seenaa M.; Aljaff, Parekhan M. (Sulaimani Journal for Pure and Applied Sciences, 2021)
Kohl is a traditional eyeliner widely used among Middle East people. There is a growing concern about using Kohl due to its potential human health risks. Over the last decades, Kohl has gained a bad reputation due to its high contamination with microorganisms and the high concentration of heavy metals. This descriptive study aims to detect the microbial content and some heavy metals concentration such as lead and Antimony in kohl samples available in the local markets of Sulaimani city. Detection of microbial content was done by using six different types of culture media and gram staining techniques with some biochemical tests, and the final identification was done by the automated system VITEK 2. The analytical test for heavy metals was performed by using an Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES). The results showed that two samples were contaminated with uncommon gram-negative bacteria (Pantoea agglomerans and Dilftia acidovorans) and one with gram-positive bacteria (Bacillus mycoides) while there is no evidence for fungal contamination. The concentrations of lead in the two samples were over the limit with a remarkable concentration of 1491 and 1117 ppm. Also, an unacceptable concentration of Antimony was recorded in one sample with 10.65 ppm. According to our results, the brands of the kohl that are sold in Sulaimani city are not safe for use because it might serve as a vehicle for the transmission of potentially pathogenic organisms or loaded with heavy metal. Therefore, this cosmetic product must be thoroughly evaluated for safety before marketing.
Keywords: Kohl; heavy metals; bacteria; identification; visible cell count; contamination